Preparation method of negative electrode
By using a combination of carboxymethylcellulose sodium and toughening agent, the problem of insufficient brittleness and adhesion of thick electrodes is solved, the high flexibility and strength of the electrodes are achieved, the production cost is reduced, and suitable for large-scale production is also provided. Maintain performance during charge and discharge.
Patent Information
- Application Number
- CN202411666879.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2024-12-20
AI Technical Summary
Due to the brittleness and poor adhesion of high-capacity thick electrodes, the flexibility of the electrode/battery is reduced, which poses safety risks. The prior art uses high crystallinity PVDF adhesives to increase production costs and complexity, and are prone to brittle breakage.
Using a combination of carboxymethylcellulose sodium, auxiliary binder and toughener, it has a rigid chain structure and a flexible copolymer chain structure, and is mixed and coated on the surface of the current collector by mechanical homogenization. After drying, the negative electrode is prepared to prevent The electrode cracked.
It realizes the prevention of electrode cracking on the basis of thick electrodes, improves the flexibility and bonding strength of the electrodes, reduces production costs and complexity, is suitable for large-scale production, and maintains performance during charging and discharging.
Smart Images

Figure CN119170804A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a negative electrode. Background Art
[0002] Lithium-ion batteries have the characteristics of high energy density, long cycle life, high safety, and wide operating temperature, and are currently widely used in various industries. In order to meet this urgent need, increasing the thickness of the electrode is one of the most direct ways to increase the energy density of lithium-ion batteries. However, due to its brittleness and poor adhesion, the high-capacity thick electrode leads to a significant decrease in the flexibility of the electrode / battery, and even the quality of the positive and negative electrode slurry preparation of lithium-ion batteries directly affects the quality of the battery and the performance of its products.
[0003] The prior art discloses an electrode for a secondary battery and a method for manufacturing the same, the electrode comprising a current collector for transferring electrons between an external wire and an electrode active material and an electrode mixture layer applied to the current collector, wherein the electrode mixture layer comprises a cross-linked polymer, an electrode active material and a binder, wherein the cross-linked polymer is a high molecular polymer having an interpenetrating network structure formed by cross-linking a first polymerized monomer and a second polymerized monomer. However, this will increase the overall production cost and the complexity and difficulty of the production line. In addition, the prior art mostly uses PVDF as a binder, but the crystallinity of PVDF homopolymer can reach 65% to 78%, and a binder with high crystallinity is prone to brittle fracture during the use of the battery, which poses a great safety hazard. Therefore, it is urgent to develop a new and effective composite binder that can prevent the electrode from having brittle ends during use on the basis of preparing thick electrodes. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a negative electrode. The electrode prepared by the method provided by the present invention can ensure that the electrode is thick and prevents the electrode from cracking during use.
[0005] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a negative electrode, comprising the following steps: mixing the negative electrode active material, the conductive agent and water to obtain a solid slurry; The solid slurry, sodium carboxymethyl cellulose, an auxiliary binder, a toughening agent and water are mixed to obtain a slurry; the auxiliary binder has a rigid chain structure, and the toughening agent has a flexible copolymer chain structure; The slurry is coated on the surface of a current collector and dried to obtain the negative electrode.
[0006] Preferably, the negative electrode active material comprises graphite and / or silicon carbon; The conductive agent includes one or more of Ketjen black, acetylene black, graphene and carbon nanotubes.
[0007] Preferably, the mass ratio of the negative electrode active material to the conductive agent is 80-106:1; The mass ratio of the total mass of the negative electrode active material and the conductive agent in the solid slurry to the mass of water is 0.8-1.5:1.
[0008] Preferably, the negative electrode active material, the conductive agent and the water are mixed by mechanical homogenization, the frequency of the mechanical homogenization is 50-90 Hz, and the time is 1-5 hours.
[0009] Preferably, the auxiliary binder includes one or more of water-based PVDF, water-based 136D, styrene-butadiene copolymer, sodium polyacrylate, sodium alginate, polyvinyl pyrrolidone, polyvinyl butyral, hydroxypropyl methylcellulose, polytetrafluoroethylene and carboxymethyl chitosan.
[0010] Preferably, the toughening agent includes one or more of acrylic emulsion, styrene acrylic emulsion, ethylene-vinyl acetate copolymer emulsion, chloroprene rubber emulsion, polyurethane emulsion and polyvinyl acetate emulsion.
[0011] Preferably, the mass percentage of the negative electrode active material in the slurry is 90-98%, the mass percentage of the conductive agent is 0.9-1.3%, and the total mass of sodium carboxymethyl cellulose, auxiliary binder and toughening agent accounts for 0.7-9.1% of the mass of the slurry.
[0012] Preferably, the coating conditions include: using a 1000 μm scraper and coating at a speed of 3 to 8 cm / s; The coating amount is 0.3-0.7 mL / cm 2 .
[0013] Preferably, the drying comprises sequentially performing a first drying and a second drying; The first drying temperature is 60-90°C and the time is 10-30 minutes; The temperature of the second drying is 60-90° C., the time is 12-24 hours, and the second drying is performed under vacuum conditions.
[0014] Preferably, the negative electrode loading is greater than or equal to 50 mg / cm 2 .
[0015] The present invention provides a method for preparing a negative electrode, comprising the following steps: mixing a negative electrode active material, a conductive agent and water to obtain a solid slurry; mixing the solid slurry, sodium carboxymethyl cellulose, an auxiliary binder, a toughening agent and water to obtain a slurry; the auxiliary binder has a rigid chain structure, and the toughening agent has a flexible copolymer chain structure; the slurry is coated on the surface of a current collector, and the negative electrode is obtained after drying. The present invention combines a binder with a rigid chain structure and a toughening agent with a flexible copolymer chain. The resulting system has high flexibility, so that it can not only provide good bonding strength, but also play a toughening role in the electrode material to prevent the thick electrode from cracking during coating and charging and discharging. At the same time, it has the characteristics of simple process, low cost, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is an optical photograph of the negative electrode obtained in Example 1; Figure 2 This is a scanning electron microscope photograph of the negative electrode obtained in Comparative Example 1; Figure 3 is a scanning electron microscope photograph of the negative electrode obtained in Example 1; Figure 4 Cyclic voltammetry curves of lithium-ion batteries assembled with negative electrodes obtained in Example 1 and Comparative Example 1; Figure 5 Impedance curves of lithium-ion batteries assembled with negative electrodes obtained in Example 1 and Comparative Example 1; Figure 6 Optical photographs of the negative electrodes obtained in Example 1 and Comparative Example 1 before and after being bent 5000 times; Figure 7 This is an optical microscope photograph of the negative electrode obtained in Comparative Example 1 after being bent 5000 times; Figure 8 This is an optical microscope photograph of the negative electrode obtained in Example 1 after being bent 5000 times; Fig. 9 This is an optical photograph of the negative electrode obtained in Example 2 after being bent 5000 times; Fig.10 This is an optical microscope photograph of the negative electrode obtained in Example 2 after being bent 5000 times. DETAILED DESCRIPTION
[0017] The present invention provides a method for preparing a negative electrode, comprising the following steps: mixing the negative electrode active material, the conductive agent and water to obtain a solid slurry; The solid slurry, sodium carboxymethyl cellulose, an auxiliary binder, a toughening agent and water are mixed to obtain a slurry; the auxiliary binder has a rigid chain structure, and the toughening agent has a flexible copolymer chain structure; The slurry is coated on the surface of a current collector and dried to obtain the negative electrode.
[0018] The present invention mixes the negative electrode active material, the conductive agent and water to obtain a solid slurry.
[0019] In the present invention, the negative electrode active material preferably includes graphite and / or silicon carbon; the conductive agent preferably includes one or more of Ketjen black, acetylene black, graphene and carbon nanotubes. In the present invention, the carbon nanotubes are preferably used in the form of a carbon nanotube dispersion, and the mass concentration of the carbon nanotube dispersion is preferably 10%.
[0020] In the present invention, the mass ratio of the negative electrode active material to the conductive agent is preferably 80-106:1; the mass ratio of the total mass of the negative electrode active material and the conductive agent to water is preferably 0.8-1.5:1, and more preferably 1:1. In the present invention, the mixing method is preferably mechanical homogenization, the frequency of the mechanical homogenization is 50-90 Hz, specifically 50 Hz, 60 Hz, 70 Hz, 80 Hz, 90 Hz; the time is preferably 1-5 hours; the mechanical homogenization is preferably carried out in a ball mill, a sand grinder or a disperser.
[0021] After obtaining the solid slurry, the present invention mixes the solid slurry, sodium carboxymethyl cellulose, an auxiliary binder, a toughening agent and water to obtain slurry.
[0022] In the present invention, the auxiliary binder preferably includes one or more of water-based PVDF, water-based 136D, styrene-butadiene copolymer (SBR), sodium polyacrylate (NaPA), sodium alginate (SA), polyvinyl pyrrolidone (PVP), polyvinyl butyral (PVB), hydroxypropyl methylcellulose (HPMC), polytetrafluoroethylene (PTFE) and carboxymethyl chitosan (CC).
[0023] In the present invention, the toughening agent preferably includes one or more of acrylic emulsion, styrene acrylic emulsion, ethylene-vinyl acetate copolymer emulsion, chloroprene rubber emulsion, polyurethane emulsion and polyvinyl acetate emulsion.
[0024] In the present invention, the mixing process preferably includes: first mixing sodium carboxymethyl cellulose and water to obtain a sodium carboxymethyl cellulose solution; secondly mixing the auxiliary binder and water to obtain an auxiliary binder solution; The solid slurry, the sodium carboxymethyl cellulose solution and the auxiliary binder solution are mixed for the third time to obtain a mixed system; The mixed system and the toughening agent are mixed for the fourth time.
[0025] In the present invention, the mass concentration of the sodium carboxymethyl cellulose solution is preferably 3-7%, specifically 3%, 4%, 5%, 6%, 7%. In the present invention, the first mixing is preferably carried out under stirring, the stirring speed is preferably 1000 rpm, and the time is preferably 2-6 hours.
[0026] In the present invention, the mass concentration of the auxiliary binder solution is preferably 2-5%, specifically 2%, 3%, 4%, 5%. In the present invention, the second mixing is preferably carried out under stirring, the stirring speed is preferably 1000 rpm, and the time is preferably 2-6 hours.
[0027] In the present invention, the mass of the sodium carboxymethyl cellulose solution is preferably 2-5% of the mass of the solid slurry, specifically 2%, 3%, 4%, 5%; the mass of the auxiliary binder solution is preferably 40-60% of the mass of the solid slurry, specifically 40%, 50%, 60%. In the present invention, the third mixing is preferably carried out under stirring, the stirring speed is preferably 1000 rpm, and the time is preferably 2-6 hours.
[0028] In the present invention, the mass of the toughening agent is preferably 1-5‰ of the mass of the mixed system, specifically 1‰, 2‰, 3‰, 4‰, 5‰. In the present invention, the fourth mixing is preferably carried out under stirring, the stirring speed is preferably 1000rpm, and the time is preferably 24-48h.
[0029] In the present invention, the mass percentage of the negative electrode active material in the slurry is preferably 90-98%, the mass percentage of the conductive agent is preferably 0.9-1.3%, and the total mass of the sodium carboxymethyl cellulose, auxiliary binder and toughening agent preferably accounts for 0.7-9.1% of the mass of the slurry.
[0030] After obtaining the slurry, the present invention coats the slurry on the surface of the current collector and obtains the negative electrode after drying.
[0031] In the present invention, the current collector preferably comprises copper foil.
[0032] In the present invention, the coating conditions preferably include: using a 1000 μm scraper and coating at a speed of 3 to 8 cm / s; the coating amount is preferably 0.3 to 0.7 mL / cm 2 , more preferably 0.5 mL / cm 2In the present invention, the drying preferably includes first drying and second drying in sequence; the temperature of the first drying is preferably 60-90°C, the time is preferably 10-30 minutes, and the first drying is preferably carried out in a blast drying oven; the temperature of the second drying is preferably 60-90°C, the time is preferably 12-24 hours, and the second drying is preferably carried out under vacuum conditions.
[0033] In the present invention, the negative electrode loading is greater than or equal to 50 mg / cm 2 .
[0034] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0035] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1 2.886 g of graphite, 0.15 g of a carbon nanotube dispersion with a mass concentration of 10%, and 0.012 g of acetylene black were mixed to obtain a mixture; then water of the same mass as the mixture was added, and mixed evenly by solid phase homogenization at a frequency of 70 Hz for 2 hours to obtain a solid slurry; Dissolve 1 g of sodium carboxymethyl cellulose in 19 g of water and stir at 1000 rpm for 2 h to obtain a sodium carboxymethyl cellulose solution with a mass concentration of 5%; 5 g of 136D (6 wt%) was added to 5 g of water and stirred at 1000 rpm for 2 h to obtain an auxiliary binder solution with a mass concentration of 3%; 0.3 g of sodium carboxymethyl cellulose solution and 2.88 g of auxiliary binder solution were added to 6.096 g of solid slurry, and stirred at a rotation speed of 1000 rpm for 2 h to obtain a mixed system; 0.0185 g of styrene-acrylic emulsion was added to 9.276 g of the mixed system, and the mixture was stirred at a speed of 1000 rpm for 24 h to obtain a slurry; With copper foil as the current collector, a 1000μm scraper was used to take 10mL of slurry and coat it at a speed of 5cm / s. The coating amount was 0.5mL / cm 2 Then it was placed in a 90°C blast drying oven for rapid drying for 20 min, and then transferred to a 90°C vacuum drying oven for 12 h to obtain a loading of 51 mg / cm 2 of the negative electrode.
[0037] Example 2 2.886 g of graphite, 0.15 g of a carbon nanotube dispersion with a mass concentration of 10%, and 0.012 g of acetylene black were mixed to obtain a mixture; then water of the same mass as the mixture was added, and mixed evenly by solid phase homogenization at a frequency of 70 Hz for 2 hours to obtain a solid slurry; Dissolve 1 g of sodium carboxymethyl cellulose in 19 g of water and stir at 1000 rpm for 2 h to obtain a sodium carboxymethyl cellulose solution with a mass concentration of 5%; 5 g of 136D (6 wt%) was added to 5 g of water and stirred at 1000 rpm for 2 h to obtain an auxiliary binder solution with a mass concentration of 3%; 0.3 g of sodium carboxymethyl cellulose solution and 2.88 g of auxiliary binder solution were added to 6.096 g of solid slurry, and stirred at a rotation speed of 1000 rpm for 2 h to obtain a mixed system; 0.009 g of polyurethane emulsion and 0.009 g of styrene-acrylic emulsion were added to 9.276 g of the mixed system, and stirred at a speed of 1000 rpm for 24 h to obtain a slurry; With copper foil as the current collector, a 1000μm scraper was used to take 10mL of slurry and coat it at a speed of 5cm / s. The coating amount was 0.5mL / cm 2 Then it was placed in a 90°C blast drying oven for rapid drying for 20 min, and then transferred to a 90°C vacuum drying oven for 12 h to obtain a loading of 53 mg / cm 2 of the negative electrode.
[0038] Comparative Example 1 The negative electrode was prepared in the same manner as in Example 1, except that no styrene acrylic emulsion was added.
[0039] Performance Testing Test Example 1 Figure 1 This is an optical photograph of the negative electrode obtained in Example 1; Figure 2 This is a scanning electron microscope photograph of the negative electrode obtained in Comparative Example 1; Figure 3 is a scanning electron microscope photograph of the negative electrode obtained in Example 1; Figures 1 to 3 It can be seen that the surface of the negative electrode with the toughening agent added is uniform and there is no cracking, while the surface of the negative electrode without the toughening agent added has cracks.
[0040] Test Example 2 The negative electrodes obtained in the embodiments and comparative examples were assembled into lithium-ion batteries, and the electrochemical performance was tested; The assembly process is as follows: first place the positive electrode shell, then place the negative electrode sheet at the center and drip 20μL LB-299 (LiPF6 / EC:EMC=3:7 wt% / 2%VC) at the center, then place the separator and drip 20μL LB-299 at the center, then place the lithium metal sheet and stainless steel gasket at the center in turn, and finally cover the negative electrode shell and use a punch to compact it to successfully assemble the button lithium-ion battery.
[0041] Figure 4 The cyclic voltammetry curves of the lithium ion batteries assembled with the negative electrodes obtained in Example 1 and Comparative Example 1 are shown in Table 1. Figure 4 It can be seen that adding a toughening agent will basically have no effect on the performance of the negative electrode.
[0042] Figure 5 The impedance curves of the lithium-ion batteries assembled with the negative electrodes obtained in Example 1 and Comparative Example 1 are as follows: Figure 5 It can be seen that adding a toughening agent will basically not affect the impedance of the battery.
[0043] Test Example 3 Figure 6 The optical photos of the negative electrodes obtained in Example 1 and Comparative Example 1 before and after the 5000-fold test, wherein the comparison sample is Comparative Example 1 and the sample is Example 1. Figure 6 It can be seen that the negative electrode with the toughening agent added remained basically unchanged before and after bending, while the negative electrode without the toughening agent added cracked and fell off after the bending test.
[0044] Figure 7 This is an optical microscope photo of the electrode obtained in Comparative Example 1 after being bent 5000 times. Figure 8 This is an optical microscope photo of the negative electrode obtained in Example 1 after being bent 5000 times. Figure 7 and Figure 8 It can be seen that the negative electrode with the toughening agent added shows extremely strong toughness compared to the negative electrode without the toughening agent added, and no cracking or falling off occurs.
[0045] Test Example 4 Fig. 9 This is an optical photograph of the negative electrode obtained in Example 2 after being bent 5000 times. Fig.10 This is an optical microscope photo of the negative electrode obtained in Example 2 after being bent 5000 times. Fig. 9 and Fig.10 It can be seen that the negative electrode with the toughening agent added did not crack or fall off after the bending test.
[0046] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode, characterized in that: The following steps are involved: mixing the negative electrode active material, the conductive agent and water to obtain a solid slurry; The solid slurry, sodium carboxymethyl cellulose, an auxiliary binder, a toughening agent and water are mixed to obtain a slurry; the auxiliary binder has a rigid chain structure, and the toughening agent has a flexible copolymer chain structure; The slurry is coated on the surface of a current collector and dried to obtain the negative electrode.
2. The preparation method according to claim 1, characterized in that: The negative electrode active material includes graphite and / or silicon carbon; The conductive agent includes one or more of Ketjen black, acetylene black, graphene and carbon nanotubes.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the negative electrode active material to the conductive agent is 80-106:1; The mass ratio of the total mass of the negative electrode active material and the conductive agent in the solid slurry to the mass of water is 0.8-1.5:
1.
4. The preparation method according to claim 1, characterized in that: The negative electrode active material, the conductive agent and the water are mixed by mechanical homogenization, the frequency of the mechanical homogenization is 50-90 Hz, and the time is 1-5 hours.
5. The preparation method according to claim 1, characterized in that: The auxiliary binder includes one or more of water-based PVDF, water-based 136D, styrene-butadiene copolymer, sodium polyacrylate, sodium alginate, polyvinyl pyrrolidone, polyvinyl butyral, hydroxypropyl methylcellulose, polytetrafluoroethylene and carboxymethyl chitosan.
6. The preparation method according to claim 1, characterized in that: The toughening agent includes one or more of acrylic emulsion, styrene acrylic emulsion, ethylene-vinyl acetate copolymer emulsion, chloroprene rubber emulsion, polyurethane emulsion and polyvinyl acetate emulsion.
7. The preparation method according to claim 1, characterized in that: The mass percentage of the negative electrode active material in the slurry is 90-98%, the mass percentage of the conductive agent is 0.9-1.3%, and the total mass of sodium carboxymethyl cellulose, auxiliary binder and toughening agent accounts for 0.7-9.1% of the mass of the slurry.
8. The preparation method according to claim 1, characterized in that: The coating conditions include: using a 1000 μm scraper and coating at a speed of 3 to 8 cm / s; The coating amount is 0.3-0.7 mL / cm 2 .
9. The preparation method according to claim 1, characterized in that: The drying comprises sequentially performing a first drying and a second drying; The first drying temperature is 60-90°C and the time is 10-30 minutes; The temperature of the second drying is 60-90° C., the time is 12-24 hours, and the second drying is performed under vacuum conditions.
10. The preparation method according to claim 1, characterized in that: The negative electrode loading is greater than or equal to 50 mg / cm 2 .
Citation Information
Patent Citations
Negative electrode slurry composition and application
CN114583173A
Lithium ion battery negative electrode binder, negative electrode plate and lithium ion battery
CN114864941A
Cathode thick electrode and preparation method and application thereof
CN115347192A
